The Influence of Card Sort Learning Media on Stuidents’ Learning Outcomes in Subtheme 1 How Clean Air Processes by Body in Grade V UPTD SDN 122337 Pematang Siantar - Rosiana Hutabalian; Lisbet Novianti Sihombing; Desi Sijabat (International Journal of Integrated Science and Technology, 2023)
This research aims to determine whether there is an influence of Card Sort Learning Media on student learning outcomes in theme 2, sub-theme 1, how the body processes clean air. In class V UPTD SD Negeri 122337 Pematang Siantar, the method in this research is a quantitative method, experimental type, which takes the form of a research design. is a pre-experimental type one group pretest-posttest. Conducted in October 2023, the population of all students at UPTD SD Negeri 12 2337 Pematang Siantar and the sample used was a saturated sample of 30 student. The variant used is two research variables: dependent variable (x) learning media and Card Sort (y) student learning outcomes , data collection techniques, namely test techniques with validity tests, reliability tests, difficulty level tests, and distinguishing power tests. Test results using the Normality test, Homogeneity test and the N-gain technique with the help of the SPSS version 21 program, based on the calculation results obtained the l homogeneity l ni l bag test by using the l Le l ve l ne l di l pe test l role l h ni l lai l si l gni l fi l kan sel l be l sar 0.097 yai l tu le l bi l h be l sar of l t table l l 0.05. So it is also with the results of l l ni l lai l pre l te l st which me l m l li l ki l average 46.33 while on the results of l l postte l st ni l la l the average is 82.83 ni l la lai l pe l rbandi l ngan or to l nai l kan from l ni l lai l pre l te l st to l postte l st yai l u 36% While the results of the l l test l N-Gai l n me l mpe l role l h ni l la l Me l an 0.76 then if l ka di l li l hat of l ti The level of gni l fi l can be grouped into categories of categories l e l fe l kti l f . So it can be concluded that there is an influence on the use of media in the Card Sort learning lesson on the learning outcomes of self - employed students on topic 2 , subsection 1 to l las V di l UPTD SD Ne l ge l ri l 12237 Pe l ripe Si l inter.